Mortalities Profile among Dubai Population 2017, Utilizing Breakdown Fractions for Intervention and Forecasting of Future Epidemiologic Transition - Dubai, UAE 2019 - Hussain, Hamid Yahya; Salim, Nazar; Zadeh, Massoumeh; Al Mehairi, Amna; Das, Kaltar (International Journal of Medical and Health Sciences Research, 2019)
Background: Mortalities and morbidities are recognized as a major statistics for health and disease measurements at any given population setting. Health care system performance is often linked to morbidity and mortality measurement as a direct quantitative outcome, Objectives: To study the mortality distribution among Dubai population. To study future interventions and forecasting of population mortalities in Dubai. Methodology: A retrospective record review of the Dubai Annual Statistical Report for the year 2017 has been carried out. All secondary data collected from 2008- 2017 related to outpatient and inpatient visits at Dubai Health Authority, Dubai Health Care City, Ministry of Health and private sector facilities in Dubai were included. Results: The current study revealed that almost one third of mortalities among Dubai Population or 30.4% were due to cardiovascular relevant causes. While 11.3% of mortalities was due to respiratory related diseases such as Pneumonia, COPD and others 6.9% were injuries related mortalities, 19.8% were neoplastic related diseases, 6.4% were accounted to perinatal period diseases and 1.2% were due to septicemia.. Conclusions: Mortality interventions and forecasting in the Population of Dubai can be made through Projections that represents a set of three visions for the future population health, based on certain explicit assumptions. Although, the wide uncertainty ranges around future projections, they enable health care system decision and policy makers to appreciate better the implications for health and health policy of currently observed trends, and the likely impact of future trends, such as the ageing population.